Self-esteem conditions at the elementary school level in the state of Sinaloa, Mexico - Luz María Meléndez Llanes,; José Antonio Soto Bernal,; Adrián Meza Laveaga,; Clara Alejandra Beltrán Fierros,; Tomás Báez Puerta,; Emeterio López López,; Juana María Armenta Trasviña,; Rocío Cervantes Cervantes, (Technium Social Sciences Journal, 2024)
At the basic school level, students go through personal and academic situations that cause them tension or discomfort when it is necessary to face facts, due the lack of social skills to give solution to problems, they lack the capacity to communicate feelings and emotions to people in a correct way, and thus reach an acceptable agreement for all the people involved. The present research has the objective of analyzing the conditions of self-esteem in the basic education environment in the state of Sinaloa, considering the factors that intervene and the changing context, as well as the intervention of the teacher. Faced with this diversity of situations, it is essential that the teachers implement strategies and innovative activities that help students to develop their knowledge, communication skills, confidence and security oriented to planned educational objectives, therefore, it is important to know each of the students in their ways of thinking to develop activities that contribute to their training. The limitations in self-esteem are linked to the cultural context in which individuals have grown and the behavior of this type can be molded in the educational processes.